(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The impact of the 2022 earthquake in Cianjur Regency continues to be felt, particularly by MSME (Micro, Small, and Medium Enterprises) actors in the affected areas such as Nagrak Village, Cianjur. In the last three years, sales of MSME products have drastically declined. Three years after the disaster, MSME actors formed a product marketing community under a souvenir outlet called Mochi Momi, initiated by Mrs. Ai Yani Nourmayani. However, the community still relies on offline sales, with sales increases occurring only on weekends, national holidays, or school holidays, when most visitors purchase typical Cianjur souvenirs. With a monthly turnover of approximately IDR 177 million, divided among around 77 active MSME members, the average turnover per MSME remains relatively low at around IDR 2,300,000 per month. Through the Community Partnership Empowerment Program (PKM) conducted by the Research and Community Service Institute (LPPM) of Universitas Putra Indonesia, an assessment-based initiative was carried out to provide digital marketing management assistance, community organizational strengthening, and website development as a digital marketing space for the Mochi Momi MSME community. This program was funded by the Ministry of Education, Culture, Research, and Technology through the Directorate of Research, Technology, and Community Service (DRTPM) in 2025. The general objectives of this Community Partnership Empowerment Program (PKM) program are to enhance sustainable and inclusive economic growth with full stakeholder participation, reduce economic productivity disparities and limited opportunities for communities to engage in digital marketing, and strengthen MSME community organizations to foster independence. The program also aligns with efforts to build peaceful and inclusive communities for sustainable development, ensuring equitable access, and strengthening local institutions with effective, accountable, and transparent governance systems. The methodology applied in this community service program utilized a participatory development approach that positioned the community as the main subject in program design and implementation. Methods included assessment, FGDs, location surveys, partner potential mapping, training workshops, monitoring, and evaluation. The Community Partnership Empowerment Program (PKM) program resulted in the creation of a website (www.umkmmochimomi.com), development of partners’ skills in website operation, content management (photos/videos/product descriptions), e-commerce transactions, as well as improved knowledge in product quality and packaging for global markets, and organizational management of the MSME community. This program is expected to enhance members’ knowledge and skills in adapting to e-commerce technology, expanding product marketing reach, and shifting from conventional to digital marketing to increase sales turnover and product promotion.